ISTIDRAJ DALAM TAFSIR AL-JILANI KARYA SYAIKH ABDUL QADIR AL-JILANI - Ilmaya, Luthfi; Miftarah Ainul Mufid; Ahmad Zainuddin; M. Mukhid Mashuri (Cahaya Ilmu Bangsa Institute, 2024)
Abstract This research was conducted against the background of human concerns, especially believers, when they have an abundance of wealth or worldly pleasures in any form. Some people are worried that the worldly pleasures they have will become istidraj for them. In this research, we also discuss istidraj according to the views of Shaykh Abdul Qadir al-Jilani. This research was conducted with the aim of knowing the concept of the Koran regarding Istidraj and knowing the opinion of Shaykh Abdul Qadir al-Jilani in his work, Tafsir al-Jilani, regarding Istidraj. This research is a type of library research. This research uses the thematic or maudhu'i method. In Tafsir al-Jilani, the theme of istidraj is explained by interpreting the verses of the Koran which discuss istidraj with the characteristics of monotheism or mysticism. The definition of istidraj in al-Jilani's interpretation is a test in the form of worldly pleasures and pleasures given to people who disobey God's commands, these pleasures can make people more negligent towards their Lord and make them further away from God's grace. People who receive istidraj will be given sudden punishment when they are careless in their enjoyment. He gave directions on how humans should respond to worldly pleasures so that they do not become istidraj for humans. Keywords: Istidraj, Tafsir Al-Jilani, Shaykh Abdul Qadir Al-Jilani.